Deformation mechanisms of human amnion: Quantitative studies based on second harmonic generation microscopy. Issue 9 (25th June 2015) - Mauri, Arabella; Ehret, Alexander E.; Perrini, Michela; Maake, Caroline; Ochsenbein-Kölble, Nicole; Ehrbar, Martin; Oyen, Michelle L.; Mazza, Edoardo
Abstract Multiphoton microscopy has proven to be a versatile tool to analyze the three-dimensional microstructure of the fetal membrane and the mechanisms of deformation on the length scale of cells and the collagen network. In the present contribution, dedicated microscopic tools for in situ mechanical characterization of tissue under applied mechanical loads and the related methods for data interpretation are presented with emphasis on new stepwise monotonic uniaxial experiments. The resulting microscopic parameters are consistent with previous ones quantified for cyclic and relaxation tests, underlining the reliability of these techniques. The thickness reduction and the substantial alignment of collagen fiber bundles in the compact and fibroblast layer starting at very small loads are highlighted, which challenges the definition of a reference configuration in terms of a force threshold. The findings presented in this paper intend to inform the development of models towards a better understanding of fetal membrane deformation and failure, and thus of related problems in obstetrics and other clinical conditions.